THE WORLDWIDE WEB AND SOCIAL MEDIA AS COMMUNICATION CHANNELS FOR PROPAGATING BRAND MESSAGES OF HIGHER EDUCATION INSTITUTIONS IN THE DEVELOPING WORLD - Ahmed, Syma; Shuja, Ahmed; Chaudhry, Rehan Mahmood (European Scientific Journal, ESJ, 2014)
Rapid developments in digital technology and World Wide Web capabilities have changed the playing field for almost all the stakeholders in the private and public sectors. Internet usage has risen dramatically in the previous decade and recently, social media has introduced a new model of interaction and engagement. This evolution in the way humans interact offers implications for entities to communicate with their audience. Social media and the World Wide Web can be gainfully employed by educational institutions, especially in developing countries to effectively communicate with current and prospective students, faculty, parents, and donors. The top universities in the developed nations have already embraced this model and are effectively using social media and World Wide Web to engage students. Social media gives the ability to have ongoing and candid conversations with people, and develop mutually beneficial relationships. Organizations that are taking it seriously and using it to leverage their strengths are being rewarded. Effective use of social media for engaging target audiences can help shorten the gap between the intended brand message and the brand message that is actually received or perceived.